Characterization and Tablet Property Evaluation of Pregelatinized Starch of Teff (Eragrostis tef ) - Assefa, Fasiledes; Dilebo, Jemal; Gabriel, Tesfaye; Brhane, Yonas; Wondu, Kebede (Asian Journal of Pharmaceutical Research and Development, 2020)
Starch is a multifunctional pharmaceutical excipient in solid dosage formulations and obtained from different sources. Teff (Eragrostis tef) grain is a source of major staple food in Ethiopia and contains starch. Teff starch was extracted from milled teff flour using 0.075% sodium metabisulphite. The starch was pregelatinized at 60 oC, 70 oC and 80 oC temperatures. When characterized, the pregelatinized teff starches had enhanced physical attributes such swelling capacity, water absorption capacity, granule density, Carr’s index, Hausener’s ratio, flow rate and angle of repose. When incorporated as disintegrant in chloroquine phosphate tablet formulation at 5% and 10% concentrations, tablets containing pregelatinized teff starches showed faster disintegration time and better compressibility compared to the native starch. Tablets containing pregelatinized teff starch at 70 oC and 10% concentration had the fastest disintegration time with 7.55 min. Pregelatinization, a non-expensive type of physical starch modification can be used to enhance excipient attributes of teff starch for its use as disintegrant in tablet formulations.